EXPERIMENTAL CORRECTION OF PROTEINASE INHIBITOR IMBALANCE BY MULTIPROBIOTIC IN SALIVARY GLANDS UNDER CONDITIONS OF OBESITY - Hordiienko, L.P. (World of Medicine and Biology, 2017)
The article presents the results of the research on the use of multiprobiotic for the correction of pathological changes in the tissues of the salivary glands of 29 rats of both sexes in conditions of obesity. Experimental correction of obesity using the multiprobiotic "Symbiter Acidophilus" normalizes a proteinase inhibitor imbalance in the tissues of salivary glands. The results show the effectiveness of probiotic therapy for the prevention of the development of pathological changes in salivary glands under conditions of obesity.
Keywords: salivary glands; obesity; proteolysis; multiprobiotic